Density heterogeneity of the Earth’s crust of the Ingul megablock of the Ukrainian Shield according to the data of three-dimensional gravity modeling - V. I. Starostenko; P. Ya. Kuprienko; I.B. Makarenko; A. Savchenko; O.V. Legostaeva (Геофизический журнал, 2015)
According to the data of three-dimensional density modeling at the scale 1:200 000 the peculiarity  of the Earth’s crust structure of the Korsun-Novomirgorod pluton and Novoukrainka massif has been found as well as density distribution by depth and lateral in granitoid massifs of gabbro-anorthosites of the Ingul megablock were given in detail. Density change within the limits of suture and fault zones has been traced, their comparative characteristics has been given.